A produção do espaço urbano como processo de valorização do capital: os empreendimentos imobiliários na região sudoeste serrana do Espírito Santo - Monteiro, Rafael Santos da Luz (2023)
This work discusses the process of real estate expansion in the Sudoeste Serrana Region of Espirito Santo, based on the production of condominiums and subdivisions towards rural areas. The study area is characterized by rural activities and a strong presence of Atlantic Forest, in addition to being an immediate neighbor of the Metropolitan Region of Grande Vitória. Because of this, over time the production of condominiums and subdivisions has been appropriating the attributes present in the landscape. exotic from the region. The Sudoeste Serrana Region brings together attractive characteristics explored by the second home real estate market, which is a major agent of transformation of the landscape and responsible for the expansion of real estate production in the region. In recent years, rural space has presented new meanings with new relationships that are established through the expansion of the logic of space as a commodity. Therefore, the Sudoeste Serrana Region presents increasing complexity due to the arrival of new agents in the production of space and, through real estate production and also through the construction of new spatialities. In this sense, we examined real estate activity in the Sudoeste Serrana Region through procedures such as document consultation in public bodies, counting, classification and mapping of projects, in addition to analyzing the evolution of urban expansion and also investigating the rentier relationship that these projects seek with the annexation of natural elements of the landscape in the process of real estate appreciation of properties. Therefore, the research debates the recent dynamics of typically urban developments that advance into the rural areas of the municipalities of Marechal Floriano, Domingos Martins and Venda Nova do Imigrante.